Early-stage minimally invasive procedures decrease perihematomal endothelin-1 levels and improve neurological functioning in a rabbit model of intracerebral hemorrhage. (April 2015) - Wang, Likun; Wang, Fan; Wu, Guofeng; Shi, Jing
Abstract : Introduction: To determine the effects of minimally invasive surgery (MIS) at various stages after intracerebral hemorrhage (ICH) on perihematomal endothelin (ET)-1 levels and neurological functioning.Methods: Sixty rabbits were randomly distributed into a model control group (MC group, 30 rabbits) or a MIS group (MI group, 30 rabbits). An ICH model was established in all animals. In the MI group, ICH was evacuated by MIS at 6, 12, 18, 24, and 48 hours (six rabbits at each time point) after the ICH was established. The animals in the MC group underwent the same procedures for ICH evacuation, but with a sham operation without hematoma aspiration. All the animals were sacrificed 7 days after the ICH was established. Neurological deficit scores were determined, and the perihematomal brain tissue was removed to determine the ET-1 levels, blood–brain barrier (BBB) permeability, and brain water content (BWC). Results: The neurological deficit scores, perihematomal ET-1 levels, BBB permeability, and BWC all decreased significantly in the MI group compared to the MC group. Performing the MIS for evacuating the ICH at 6 hours resulted in the most remarkable decreases in these indices, followed by a significant difference observed at 12 hours within the MI subgroups. Conclusions: Performing MIS at 6–12 hours after ICH resulted in the most significant decreases in neurological deficit scores, ET-1 levels, BBB permeability, and brain edema. The optimal time window for performing MIS for ICH evacuation might be within 6–12 hours after hemorrhage.